2016
DOI: 10.4103/2303-9027.183978
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic endoscopic ultrasound findings of ampullary lesions that predict the need for surgical excision or endoscopic ampullectomy

Abstract: Background and Objectives:The management of ampullary lesions has evolved to include endoscopic ampullectomy (EA) as a curative approach to cancers of the ampulla of Vater. With this change comes a need to risk-stratify patients at initial diagnosis.Materials and Methods:Patients with verified ampullary lesions (N = 50) were analyzed in a case-control design. We evaluated endoscopic ultrasound (EUS) data to define characteristics that yield a high sensitivity in selecting candidates for EA.Results:Using data f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Moreover EUS helps to evaluate the depth of the tumor "T" compromise, the presence of lymph nodes "N" and vascular compromise is also evaluated. The FNA-FNB of the pancreatic mass and regional lymph nodes for cytology is occasionally required to con rm the ndings or to plan for a neoadjuvant or palliative therapy [10] This prospective cohort study included 24 patients (Table 1). Our research revealed that PC is common in patients older than 56 years old and this agrees with Michael et al [11] who said that the risk of developing pancreatic cancer increases as people age.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover EUS helps to evaluate the depth of the tumor "T" compromise, the presence of lymph nodes "N" and vascular compromise is also evaluated. The FNA-FNB of the pancreatic mass and regional lymph nodes for cytology is occasionally required to con rm the ndings or to plan for a neoadjuvant or palliative therapy [10] This prospective cohort study included 24 patients (Table 1). Our research revealed that PC is common in patients older than 56 years old and this agrees with Michael et al [11] who said that the risk of developing pancreatic cancer increases as people age.…”
Section: Resultsmentioning
confidence: 99%
“…1). Linear array EUS was used in all patients to evaluate and visualize depth of invasion as well as the intraductal invasion of the tumor and locoregional lymph node status 22–26…”
Section: Methodsmentioning
confidence: 99%
“…Linear array EUS was used in all patients to evaluate and visualize depth of invasion as well as the intraductal invasion of the tumor and locoregional lymph node status. [22][23][24][25][26] We performed endoscopic en bloc resection using a regular oval snare, without saline injection, which is a controversial practice and may cause difficulties during the placement of the snare to achieve an adequate en bloc resection. 27,28 Resection was performed with Endocut mode setting on the electrosurgical generator because the incidence of bleeding seems lower when compared with resection using a cutting current.…”
Section: Technical Detailsmentioning
confidence: 99%
“…Accuracy in determining resectability of ampullary and pancreatic cancers has been reported as 72%[ 35 ]. Rejeski et al [ 36 ] reported a set of EUS findings which detected ampullary tumours requiring surgery rather than EP with a sensitivity of 97.1%, although this was not prospectively validated on an independent data sample.…”
Section: Pre-operative Evaluationmentioning
confidence: 99%